Dysphagia and factors associated with malnutrition risk: A 5-year multicentre study - Blanař, Vít; Hödl, Manuela; Lohrmann, Christa; Amir, Yufitriana; Eglseer, Doris (Journal of advanced nursing, 2019)
AIMS: To describe the associations between dysphagia and malnutrition risk and to identify predictors for dysphagia in a group of persons at risk of malnutrition in hospitals and nursing homes. DESIGN: A secondary analysis of cross-sectional data from the years 2012-2016. METHODS: The risk of malnutrition was assessed using the Malnutrition Universal Screening Tool for Adults (MUST). The data were compared regarding malnutrition risk and dysphagia. Regression analyses were conducted to identify variables that were associated with the risk of malnutrition and dysphagia. RESULTS: Patients (N = 17,580) were included in the study sample. The prevalence of dysphagia was 6.6% and the prevalence of malnutrition risk was 18.9%. A multivariable logistic regression analysis resulted in the identification of dysphagia and cancer as variables with the highest odds ratios with regard to malnutrition risk. Patients with cancer, stroke or respiratory diseases represent a high-risk group for the co-occurrence of dysphagia and risk of malnutrition. CONCLUSIONS: Screening for dysphagia should be carried out on patients at risk of malnutrition as an integral part of their admission to a healthcare institution and especially on the higher risk group of patients with cancer, a stroke or a respiratory disease. IMPACT: What problem did the study address? This study identified the relationship between dysphagia and malnutrition risk and associated factors. What were the main findings? Dysphagia among patients in the research sample was associated with more than two times higher prevalence of the malnutrition risk. Where and on whom will the research have an impact? Thorough malnutrition risk and dysphagia screening lead to better nursing care.
Keywords: Hospitals; logistické modely; průzkumy a dotazníky; Female; nemocnice; ženské pohlaví; Logistic Models; průřezové studie; Malnutrition; Neoplasms; Surveys and Questionnaires; cévní mozková příhoda; nádory; komorbidita; lidé; Comorbidity; Stroke; podvýživa; Aged, 80 and over; Nursing Homes; Middle Aged; Risk Factors; Cross-Sectional Studies; Male; Aged; poruchy polykání; Respiratory Tract Diseases; rizikové faktory; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Deglutition Disorders; nemoci dýchací soustavy; pečovatelské domovy; Humans